Features of the Political Development of Iraq in 2003—2020: the Formation of a New Elite - R. Sh. Mamedov; M. A. Sapronova (Научный диалог)
The features of recruiting the political elite of Iraq after the overthrow of the regime of President Saddam Hussein in 2003 are considered. The relevance of the study is due to the need to study the processes of elite formation in the Middle East during the period of regional transformations. The key mechanisms and principles of the formation of the Iraqi political elite within the framework of the emerging post-Saddam political system have been identified. It is shown that the political leaders who came into power with the support of the Americans until 2003 were the “counter-elite” of S. Hussein, therefore participation in the opposition movements became an important criterion for recruiting. Special attention is paid to the informal (traditional) principles of recruiting the new elite, which have become the main mechanism of this process. In particular, the following principles are described: “muhassasa taifiyya”, which assumes the distribution of political positions in accordance with the share of ethno-confessional groups in the general population, clan solidarity, and religious institutions. It is emphasized that the role of Shiite religious structures, including spiritual leaders, and their influence on the formation of the political elite have significantly increased compared to the pre-occupation period.